Studies on the Histochemistry of the Proventriculus and Gizzard of Post-Hatch Guinea Fowl (Numida meleagris) - Selvan, P. Senthamil; Ushakumary, S.; Ramesh, Geetha (International Journal of Poultry Science, 2008)
The proventricular surface epithelial cells were positive for both acid and neutral mucins and stained intensive for acid phosphatase and adenosine triphosphatase. The proprial gland cells revealed histochemical distribution and activity of various enzymes and lipids similar to that of the submucosal gland cells. However, the ductular cells of the submucosal glands showed comparatively stronger reaction for acid phosphatase, alkaline phosphatase, adenosine triphosphatase, lipase and carbonic anhydrase except for succinic dehydrogenase. In gizzard, the koilin was positive for both acid and neutral mucin. The epithelial cells of the proprial glands stained strongly for adenosine triphosphatase and moderately for acid and alkaline phosphatases. However, their response for succinic dehydrogenase and lipase was weak. The smooth muscle cells of the proventriculus and gizzard showed a moderate to strong reaction for adenosine triphosphatase.